CARTOGRAPHIC DIGITAL BASE AS A TOOL FOR IDENTIFYING AREAS PRONE TO EROSION AND MASS MOVEMENT IN JOÃO PESSOA (PB), BRAZIL - de Oliveira Vital, Saulo Roberto (2016)
This study aims at identifying the risks of erosion and mass movement in the city of João Pessoa (PB) by using geoprocessing techniques. To do this, thematic maps comprising information about soil covering, declivity, exposure of slopes and soils were generated from OLI/Landsat images and topographic charts. Based on this information, it was possible to observe that the analyzed risks are basically represented by linear erosion and by the dismantle on the slopes and river terraces. The results obtained show a series of risks in the day to day of the population living in these areas, thus requiring actions that may mitigate or extinct theses risks. Therefore, it is understood that this issue needs more detailed studies that may help in the characterization, prediction, monitoring, recovering, and extinction of theses socio-environmental problems.